CHERNOZEM SOIL GENETIC FEATURES DIAGNOSIS WITH MAGNETIC METHODS - Kruglov, O.; Menshov, О.; Solovey, V.; Lebed', V.; Andreeva, О. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The ecological-genetic status of soil is determined by the course of the soil-forming process and is the main factor in optimizing the agricultural use to achieve a sustainable state. The definition of a qualitative indicator of this status (KVAG) is developed in Ukraine and is characterized as costing and resource intensive. To solve the problem, it is proposed to replace agrochemical methods with less costly magnetic ones. The purpose of the study is to show the informativeness of geophysical methods for the indication of the process of pedogenesis on the example of chernozems podzolized of Kharkiv region. We used the standardized studies of determination of organic carbon content, determination of the particle size distribution of soil, and pH analysis. The characteristic of the sampling site on the slope was performed by determining the erosion hazard index. The mass-specific magnetic susceptibility of soil (MS) was determined and then calculated. The study sites were located at the area of distribution of chernozems podzolized in the northern part of Kharkiv district and the central part of Pechenigy district of Kharkiv region. Soil genetic identity has been determined initially at the large-scale survey map and refined by field studies. The erosion processes complicated the soil study at the slope. We registered high informativeness of MS for the indication of genetic status. MS is relevant to use not only within a single agrocenosis, but also in agrolandscapes for soils which pedogenesis is complicated by hydromorphism. The experiment was performed at one-lane terrace of the Siverskyi Donets River, where soils of varying degrees of hydromorphism are developed. Magnetic methods have significant outlook for their application in soil studies. The example of the podzolized soils investigation of Kharkiv region shows the possibility of the identification of hydromorphic processes in the lower part of the soil profile (decrease of the values of MS compared to the background). The example of the arable land shows the possibility of replacing the high-cost determining of the humus content by much cheaper MS as the indicator of ecological-genetic status of soil (KVAG). The correlation coefficient between the KVAG and KVAMS (based on the MS measuring) is: ρ = 0.901.
Keywords: soil; magnetic susceptibility; slope; humus; hydromorphism